GROWTH AND NUTRITIONAL COMPOSITION OF ERVA-MATE AS AFFECTED BY NITROGEN, PHOSPHATE AND POTASSIUM FERTILIZATION - Delmar Santin; Eliziane Luiza Benedetti; Marília Camotti Bastos; Jéssica Fernandes Kaseker; Carlos Bruno Reissmann; Gilvano Ebling Brondani; Nairam Félix de Barros (Ciência Florestal, 2013)
http://dx.doi.org/10.5902/198050989282 Ilex paraguariensis is considered a low P-requiring species because it grows naturally in soils with low P content, although no much information is also available for N and K requirements. This trial aimed to evaluate the effect of increasing P rates, combined with N and K rates on Ilex paraguariensis growth and its mineral composition. Phosphorus rates of 0, 100, 200, 400 e 600 mg dm-3 of P2O5 were combined with 0, 50 e 100 mg dm-3 of N e K2O. The fertilizers were mixed with the soil and placed in plastic pots of 2.9 dm3. Seedlings of Ilex were transplanted to the pots and grown for 120 days. Ilex seedling growth was affected by the interaction of P and NK rates. The best P rate was between 18.5 and 28.6 mg dm-3and the highest growth was obtained when P was combined with 100 mg dm-3of N and K2O. Iron deficiency symptoms appeared at the P rates of 400 and 600 mg dm-3 of P2O5. It can be concluded that Ilex responds to increasing P rates, as long as plant N, K and Ca requirement is met.